2005
DOI: 10.28945/2891
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Critical Reflection for Postgraduate Students in Computing

Abstract: In this paper the assumption that critical reflection skills are acquired automatically during postgraduate study is queried by examining whether keeping a reflective journal is an aid in developing reflective habits. All course outlines in the postgraduate program studied for this paper state that students will learn how to critique issues relating to the topic being studied. The assumption is that critical reflection is a skill that is acquired automatically during the degree. Postgraduate students at this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
1
5
0
1
Order By: Relevance
“…Adeninyi (2011) posits that having good study habits will develop students to have a higher level of aspiration to pursue a career. Fielden (2004) also confirms that good study habits facilitate students to have higher skill outcomes. In consonance, Jones and Harlan (2005) suggest that educators need to be informed on what level the students attain independent learning skills and habits.…”
Section: Study Habits Of Applied Science Technology Studentssupporting
confidence: 59%
“…Adeninyi (2011) posits that having good study habits will develop students to have a higher level of aspiration to pursue a career. Fielden (2004) also confirms that good study habits facilitate students to have higher skill outcomes. In consonance, Jones and Harlan (2005) suggest that educators need to be informed on what level the students attain independent learning skills and habits.…”
Section: Study Habits Of Applied Science Technology Studentssupporting
confidence: 59%
“…In the Saudi context, unfortunately, there is a slow adoption of reflective practice in higher education programs (Almorshid, 2014). Although reflection as a learning concept is well-researched by scholars, its practical application, especially in terms of postgraduate students' education programs, needs to be studied thoroughly (Fielden, 2008). Consequently, this study may contribute to the academic exploration of reflective practice in the context of higher education programs.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Lidhoo and Khan (1990) observed that poor study habits and low need-achievement were associated with underachievement among bright subjects. Aisha R et al (2002) conducted a study aimed at determining the effect of study habits on the achievements of students and observed that significant and positive relationship exists between achievement and a proper study schedule while Fielden (2004) asserted that good study habits help the students in critical reflection in skills outcomes such as selecting, analyzing, critiquing, and…”
Section: Literature Reviewmentioning
confidence: 99%